2009
DOI: 10.1007/s11239-009-0316-4
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to prescribing compression stockings for patients with acute dvt: the MASTER registry

Abstract: Italian clinicians' attitudes to prescribing ES still appear suboptimal. Special attention is needed for patients treated at home, where organizational problems can interfere with the use of ES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…While age did not influence the duration of anticoagulant therapy in one study [16], older patients were more likely to have continuation of parenteral anticoagulation until INR was ≥2 for 24 hours in another study [6]. In an Italian registry, compression stockings were 1.6 times more likely to be prescribed in patients aged 40–60 years than in patients aged >80 years [31].…”
Section: Discussionmentioning
confidence: 89%
“…While age did not influence the duration of anticoagulant therapy in one study [16], older patients were more likely to have continuation of parenteral anticoagulation until INR was ≥2 for 24 hours in another study [6]. In an Italian registry, compression stockings were 1.6 times more likely to be prescribed in patients aged 40–60 years than in patients aged >80 years [31].…”
Section: Discussionmentioning
confidence: 89%
“…However, at least in Europe, compression is started already in the acute phase of DVT in the majority of cases as an adjuvant treatment modality to reduce pain and swelling as demonstrated in reviews from France and Italy. 7,8…”
Section: Compression and Walking Reduce Pain And Swelling More Than Bed Restmentioning
confidence: 99%
“…A survey performed in Canada revealed that only 26% of the physicians prescribed compression in the acute phase of DVT 20 which is quite different from the European tradition starting with compression in the vast majority of cases. 7,8 A delayed start with compression could also be one of the reasons for the negative outcome of the recent trial published by Kahn et al 20…”
Section: Logistic Problemsmentioning
confidence: 99%